The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.cell.2015.07.011
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibiting DNA Methylation Causes an Interferon Response in Cancer via dsRNA Including Endogenous Retroviruses

Abstract: Summary We show that DNA methyltransferase inhibitors (DNMTis) upregulate immune signaling in cancer through the viral defense pathway. In ovarian cancer (OC), DNMTis trigger cytosolic sensing of double-stranded RNA (dsRNA) causing a Type I Interferon response and apoptosis. Knocking down dsRNA sensors TLR3 and MAVS reduces this response twofold, and blocking interferon beta or its receptor abrogates it. Upregulation of hypermethylated endogenous retrovirus (ERV) genes accompanies the response and ERV overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

93
1,357
9
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,480 publications
(1,470 citation statements)
references
References 92 publications
93
1,357
9
11
Order By: Relevance
“…These elevated dsRNA species were mostly found in introns, corroborating known transcriptome‐wide HNRNPC binding regions (Konig et al , 2010; Zarnack et al , 2013). This differs from previous observation of elevated dsRNA derived from normally hypermethylated endogenous retroviruses (ERVs) that are activated by anti‐tumor inhibitors to trigger the IFN response as a therapeutic approach (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Heterogeneous nuclear ribonucleoprotein C is well known for its function in regulating RNA splicing by binding with introns, especially the introns containing Alu (Konig et al , 2010; Zarnack et al , 2013).…”
Section: Introductioncontrasting
confidence: 84%
See 3 more Smart Citations
“…These elevated dsRNA species were mostly found in introns, corroborating known transcriptome‐wide HNRNPC binding regions (Konig et al , 2010; Zarnack et al , 2013). This differs from previous observation of elevated dsRNA derived from normally hypermethylated endogenous retroviruses (ERVs) that are activated by anti‐tumor inhibitors to trigger the IFN response as a therapeutic approach (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Heterogeneous nuclear ribonucleoprotein C is well known for its function in regulating RNA splicing by binding with introns, especially the introns containing Alu (Konig et al , 2010; Zarnack et al , 2013).…”
Section: Introductioncontrasting
confidence: 84%
“…However, in our work done in different types of breast cancer cells, expression profiles of the down‐stream genes indicated that NOTCH3 signaling was not amplified when interferon signaling was activated. On the other hand, several other studies have reported that up‐regulated dsRNA from endogenous retrovirus (ERV) in tumor cells, triggered by DNA methyltransferase inhibitors or CDK4/6 inhibitors, induced IFN responses and thus inhibited tumor development (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Our proposed model is similar to these studies, even though the dsRNA species in our study were originated from a different resource than ERV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Mechanistically, it Chiappinelli et al demonstrated that DNMTi induce a type I interferon (IFN) response due to viral mimicry. 15 Moreover, enhanced anti-tumor immunity by combining DNMTi with HDACi involves type I IFN, MYC depletion and profound alterations in the tumor microenvironment. 9,10 …”
Section: Introductionmentioning
confidence: 99%